Analisis tingkat kesehatan keuangan perusahaan BUMN di bidang konstruksi - Elza Levina Syahda; Ningrum Pramudiati (Department of Accounting Universitas PGRI Yogyakarta, 2024)
This study analyzes State-Owned Enterprises (BUMN) financial health in the building construction sector, specifically PT. WIKA, during the period from 2017 to 2023. This analysis is conducted to improve the company's financial performance using eight financial indicators established in the Minister of BUMN Decree No: Kep-100/MBU/2002. The research results show that in 2023, PT. WIKA received the